Local Government Policies in the Management of Coastal and Marine Resources Through Community Participation - Yuhandra, Erga; Rifa’i, Iman Jalaludin; Hidayat, Sarip (Unifikasi : Jurnal Ilmu Hukum, 2023)
Natural resources are important for national development, specifically when managed effectively to generate foreign exchange. Therefore, this study aims to investigate how local governments and communities utilize and manage coastal and marine resources. It also seeks to identify the primary barriers hindering the use of such resources in achieving environmental sustainability. The study adopted a normative juridical method, focusing on examining and interpreting theoretical aspects related to legal principles, concepts, doctrines, and norms that govern the management of coastal and marine resources. Data analysis used a juridical-qualitative method, combining both descriptive-analytical and prescriptive dimensions. This qualitative method ensured consistency across legal frameworks, with careful attention paid to legal hierarchy and certainty. The process involved reviewing both written and unwritten laws to assess their alignment and legal soundness. Primary legal materials, particularly existing laws and regulations, served as the main data sources for this study. The results showed that the sustainable management of coastal and marine resources necessitates collaborative efforts among all stakeholders. To ensure effective implementation, it was essential to align and harmonize legal instruments issued at both the central and local governments. This coordination was needed to realize an optimal management of coastal and marine resources.